Search for resonant WZ production in the fully leptonic final state in proton–proton collisions at s=13TeV with the ATLAS detector - Onofre, A. (2018)
A search for a heavy resonance decaying into WZ in the fully leptonic channel (electrons and muons) is performed. It is based on proton–proton collision data collected by the ATLAS experiment at the Large Hadron Collider at a centre-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 36.1 fb−1. No significant excess is observed over the Standard Model predictions and limits are set on the production cross section times branching ratio of a heavy vector particle produced either in quark–antiquark fusion or through vector-boson fusion. Constraints are also obtained on the mass and couplings of a singly charged Higgs boson, in the Georgi–Machacek model, produced through vector-boson fusion.